MIĘDZYDOBOWE ZMIANY BODŹ COWOŚCI CIŚNIENIA ATMOSFERYCZNEGO W POZNANIU W LATACH 1988–2017 - Nawrocka, Marta; Szyga–Pluta, Katarzyna (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2018)
The aim of the paper was to investigate the stimuli of the atmospheric pressure and the dependence of large pressure changes on atmospheric circulation in Poznań. The values of the average daily atmospheric pressure from the Poznań-Ławica meteorological station in years 1988-2017 were used. The frequency of days with atmospheric pressure greater than 1015 hPa and lower than 985 hPa as well as the number of days with interdiurnal change of the atmospheric pressure were calculated in specified ranges: 0.0-4.0 hPa, 4.1-8.0 hPa, 8.1-16.0 hPa and >16.1 hPa. Next, the conditional probability of the interdiurnal changes of the air pressure and the Grosswetterlagen (GWL) types of atmospheric circulation was determined. In Poznań in 1988–2017, the most stimulus air pressure changes occurred between November and February and the least stimulus – from May to August. Strong and very strong stimulus of atmospheric pressure is most often found in cyclonic circulation types with masses of air flowing from north-western directions.